Paradigma Neoliberal dan Demokrasi Sosial dalam (Perspektif Ekonomi Islam) : Kebijakan Pengentasan Kemiskinan di Indonesia - Rispan Rispan; Isnaini Harahap; Windu Anggara (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
This study analyzes the differences between the neoliberal and social democratic paradigms in poverty alleviation policies in Indonesia, by adding an Islamic Economic perspective as an alternative. The neoliberal paradigm focuses on free market mechanisms, deregulation, and minimizing the role of the state, but often exacerbates social inequality. In contrast, the social democratic paradigm balances the role of the market and state intervention through resource redistribution and protection of vulnerable groups through sustainable social programs. Islamic economics offers a complementary approach oriented towards the principles of distributive justice, balance, and solidarity, by integrating spiritual values ​​into socio-economic policies. A qualitative approach is used in this study, with policy analysis of programs such as the Family Hope Program (PKH) and the National Health Insurance (JKN). The results show that the social democratic paradigm is more effective in reducing poverty systemically than neoliberalism, especially through increasing access to education, health, and social protection. However, budget constraints, corruption, and infrastructure gaps remain significant challenges. The Islamic Economic perspective emphasizes the importance of zakat, waqf, and infaq as instruments of wealth redistribution that have the potential to strengthen inclusive and sustainable poverty alleviation policies. This study recommends strengthening the synergy between the paradigm of social democracy and the values ​​of Islamic Economics to create policies that are more effective, equitable, and oriented towards the welfare of society holistically.